Game Edukasi Pengenalan Huruf Hiragana Untuk Meningkatkan Kemampuan Berbahasa Jepang - Nurcholis, Rifki; Purnamasari, Ade Irma; Dikananda, Arif Rinaldi; Nurdiawan, Odi; Anwar, Saeful (Forum Kerjasama Pendidikan Tinggi, 2021)
Educational games are very interesting to develop, because of the diversity that can be done. Some of the advantages of educational games compared to conventional educational methods, one of the main advantages of educational games is the visualization of real problems. Based on the pattern possessed by the game, players are required to learn so that they can solve existing problems. Game status, instructions, and tools provided by the game will guide players actively to explore information so that they can enrich their knowledge and strategies while playing. One of the interesting educational games to focus on is an educational game that discusses the introduction of foreign languages ​​focused on Japanese. With this educational game, it is hoped that it can help students to understand and memorize the hiragana letters in Japanese. This study aims to create a windows-based educational game application as an alternative medium for learning to recognize Japanese Hiragana letters. This game can later be used as an alternative learning media for the general public who just want to learn Japanese, by knowing the basics of Hiragana letters. The research method that can be used for this research can use the MDLC development method. The stages in this research process are Concept, Design, Material Collecting, Assembly, Testing, Distribution. The result of the research is an educational game of Japanese hiragana letters which introduces the basic Japanese hiragana letters and how to write them. In addition there is a quiz game of stacking letters into words to train children after knowing the basic letters of Japanese hiragana. Thus it can help children learn Japanese more easily. With this educational game, it is hoped that it can help children to understand and memorize the hiragana letters in Japanese